2010
DOI: 10.1097/01.hjh.0000378623.36731.6c
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension in a Sample of 5372 Portuguese Children and Adolescents the Aveleira Registry: PP.7.299

Abstract: Aim: In the Azerbaijan national sample, to investigate gender-specific associations between educational level and body mass parameters: body mass index (BMI), waist circumference (WC), abdominal obesity (AO), as well as the links between education and cardio-metabolic risk (CMR) components -arterial hypertension (AH) and diabetes mellitus (DM).Material and methods: The study included people 760aged 24-84 years: 290 men and 470 women. Response rate was 82,3%.Results: Higher-educated people demonstrated lower le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 0 publications
1
13
3
Order By: Relevance
“…Our results show that Cof1 also regulates actin depolymerization in the contractile ring and plays an important role in ring constraction. Although several previous studies have clearly implicated ADF/cofilin in actomyosin ring assembly and/or contraction (Coniglio et al, 2009; Hotulainen et al, 2005; Maldonado et al, 2009; Nakano and Mabuchi, 2006), the precise functional consequence of cofilin-mediated actin depolymerization in cytokinesis has been unclear. Our analysis suggests that cofilin can be a key component of the force generating machinery during cytokinesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that Cof1 also regulates actin depolymerization in the contractile ring and plays an important role in ring constraction. Although several previous studies have clearly implicated ADF/cofilin in actomyosin ring assembly and/or contraction (Coniglio et al, 2009; Hotulainen et al, 2005; Maldonado et al, 2009; Nakano and Mabuchi, 2006), the precise functional consequence of cofilin-mediated actin depolymerization in cytokinesis has been unclear. Our analysis suggests that cofilin can be a key component of the force generating machinery during cytokinesis.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] The prevalence of overweight including obesity in children in the Caribbean is high, but varies between islands. Compared with Bonaire, fewer children on St Lucia, Jamaica and Barbados are overweight, while on Aruba and Trinidad/Tobago more children are overweight.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies have reported the prevalence of hypertension in normal-weight (2-8%), overweight (4-14%) and obese (11-23%) children. [8][9][10][11] These studies used the 85th and 95th percentiles for BMI from national reference values. We used the International Obesity Task Force (IOTF) cut-off values which are accepted worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension, defined as blood pressure ≥ 95th percentile for age , is becoming increasingly common in obese children and adolescents. Several studies confirm a direct association between overweight and obesity and hypertension in children, with a prevalence of hypertension in overweight children of 4–14% and in obese children of 11–23% . This development is worrisome since both obesity and hypertension tend to track from childhood into adulthood, increasing the burden of hypertension in adults as well .…”
Section: Introductionmentioning
confidence: 99%